Oral health status and quality of life in female patients receiving low dose bone-modifying agents for cancer treatment-induced bone loss: a single-center exploratory study - Mauceri, Rodolfo; Coppini, Martina; Marchese, Sara Maria; Mauceri, Nicola; Coniglio, Rita; Nisi, Marco; Mauceri, Maria Elena; Fusco, Vittorio; Valerio, Maria Rosaria; Campisi, Giuseppina (Frontiers in Oral Health, 2025)
IntroductionBreast cancer patients, undergoing low-dose bone-modifying agent (LD-BMA) therapy for cancer treatment-induced bone loss (CTIBL), represent an emerging category at risk of Medication-Related (MRONJ) low (<1%) but not absent. However, data on their oral health status and quality of life related are currently limited. This single-center exploratory study aimed to assess oral health conditions, periodontal status, and oral health-related quality of life in non-metastatic breast cancer patients under LD-BMA therapy for CTIBL.Materials and methodsForty patients were consecutively and unselectively enrolled and divided into two groups based on the duration of LD-BMA therapy (<3 years vs. ≥3 years). Oral examination by decayed-missing-filled teeth index (DMFT) and Periodontal Screening and Recording (PSR) was performed, and the OHIP-14 questionnaire was administered to assess their oral health-related quality of life.ResultsNo statistically significant differences were observed between the two groups in PSR, DMFT, or OHIP-14 scores. PSR scores indicating moderate-to-severe periodontal involvement (3–4) were reported in 73.3% of patients treated for <3 years and 70% of those treated ≥3 years. Mean DMFT values were 9.7 and 12.0, respectively. Although patients treated for ≥3 years reported higher OHIP-14 scores, this trend did not reach statistical significance. No cases of MRONJ were observed in the study groups.ConclusionsPatients affected by breast cancer receiving LD-BMA therapy for CTIBL and recruited in a preventive program appear to have a very low risk of MRONJ. Despite comparable clinical findings across treatment durations, longer LD-BMA therapy may be associated with a perceived reduction in oral well-being, possibly related to systemic and psychosocial burdens. These findings, with the limitation of a small sample size, support the implementation of individualized, risk-based dental and psychological preventive strategies, and reinforce the relevance of long-term dental surveillance in this under-explored population.